Kedudukan Keponakan sebagai Ahli Waris Pengganti terhadap Harta Warisan Berdasarkan Kitab Undang-Undang Hukum Perdata - Maharati, Dinda Devina (International Forum of Researchers and Lecturers, 2025)
The position of nephews as substitute heirs in inheriting inheritance often raises questions because they do not have direct blood relations with the testator. However, the Civil Code has regulated the provisions of inheritance by substitute heirs. This research examines what is meant as inherited property, how are the provisions of substitute heirs in the Civil Code, and what is the position of nephews as substitute heirs to inherited property. The purpose of this research is to provide an analysis related to the position of nephews as substitute heirs so that it can be a reference in the process of dividing the inheritance. This research uses normative research methods with a statutory approach. The results of the research show that the Civil Code has regulated and guaranteed that nephews as substitute heirs can have the right to receive inheritance from the testator.